2019
DOI: 10.1002/lio2.260
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of human papilloma virus, p16, and epstein‐barr virus in non‐malignant tonsillar disease

Abstract: Objectives Due to their location in the entrance of the aero‐digestive tract, tonsils are steadily exposed to viruses. Human papilloma virus (HPV) and Epstein‐Barr virus (EBV) are two potentially oncogenic viruses that tonsils encounter. The incidence of HPV positive tonsillar cancer is on the rise and it is unknown when infection with HPV occurs. Aim To investigate if tonsils are infected with HPV and EBV, to study the co‐expression of HPV and its surrogate marker p16,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…In a study of patients with nonmalignant tonsils, of the above viruses, only DNA-EBV was detected in more than half of the samples. The authors concluded that HPV and EBV infected independently of each other [ 60 ]. Interestingly, in vitro studies suggest that in the case of coinfection in oral squamous epithelial cells, the presence of HPV may increase the pathogenesis of EBV [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients with nonmalignant tonsils, of the above viruses, only DNA-EBV was detected in more than half of the samples. The authors concluded that HPV and EBV infected independently of each other [ 60 ]. Interestingly, in vitro studies suggest that in the case of coinfection in oral squamous epithelial cells, the presence of HPV may increase the pathogenesis of EBV [ 44 ].…”
Section: Discussionmentioning
confidence: 99%